Attitudes and practices toward feral cats of male and female dog or cat owners and non-owners in Seoul, South Korea - Kim, Sun-A.; Kenyon, Claire J.; Cheong, Sejin; Lee, Jenna; Hart, Lynette A. (Frontiers in Veterinary Science, 2023)
The number of pet cats in South Korea has sharply increased since 2010. Problems have arisen with feral or stray cats, creating conflict among residents, to such an extent that the government provides some sites for people to offer feeding stations for the stray cats. This study investigated hypotheses on people’s attitudes toward feral cats in Seoul, South Korea: (i) dog and cat owners would show more positive attitudes than non-owners toward feral cats; (ii) females would have more positive attitudes toward feral cats than males; (iii) the number of Seoul-provided feeding stations by district would be correlated with people’s positive attitudes toward feral cats. Responses from 7,394 participants were used for the final analyses with 3,179 males, 3,607 females, and 599 others (includes “decline to state”). Cat owners reported more extremely positive attitudes toward feral cats than people who had no cats. Females more often had cats than males, and they were more extremely positive toward pet and feral cats than males, and strongly opposed to culling as a management strategy. The attitudes toward feral cats of people with only dogs were intermediate between people with cats and people without pets, more resembling those of people without pets. There was a correlation between the number of city-provided feeding stations and people’s attitudes toward feral cats, but only in the areas with at least 40 feeder stations; having many city-provided feeding stations was associated with very negative attitudes to feral cats. Whether the very large number of feeding stations were provided in the two neighborhoods due to a previously excessive number of feral cats in those neighborhoods, vs. those feeding stations attracting or provisioning an ever-growing number of feral cats, is unknown. These results show sharp differences in attitudes between cat owners and non-owners, and between males and females. Results resemble findings in other studies, perhaps with more extreme differences between sub-groups. The study revealed that attitudes toward pet and feral cats in Seoul were complex and varied with pet ownership, with sex, and with neighborhood context.